Extrauterine Growth Restriction in Very Low Birth Weight Infants: Concordance Between Fenton 2013 and INTERGROWTH-21st Growth Charts - González-García, Lara; García-López, Enrique; Fernández-Colomer, Belén; Mantecón-Fernández, Laura; Lareu-Vidal, Sonia; Suárez-Rodríguez, Marta; Arias-Llorente, Rosa Patricia; Solís-Sánchez, Gonzalo (Frontiers in Pediatrics, 2021)
Postnatal growth restriction has high prevalence in very low birth weight (VLBW) preterm neonates, and this could affect their long-term prognosis. Nowadays, there is no consensus on how to monitor growth in these neonates. Objective: This study aimed to compare prevalence of intra- and extrauterine growth restriction (IUGR and EUGR) in a sample of VLBW infants according to the Fenton 2013 charts and INTERGROWTH-21st (IW-21) standards and to analyze concordance between both in the different EUGR definitions criteria (cross-sectional, dynamic, and true). Patients and Methods: An observational retrospective study of 635 VLBW preterm was performed. The study was carried out in Central University Hospital of Asturias. Body measurements (weight, length, and head circumference) were collected at birth and at hospital discharge and expressed in z-scores for the two references (Fenton 2010 and IW-21). Kappa concordance was calculated. Results: Kappa concordance between Fenton and IW-21 was 0.887 for IUGR and 0.580 for static EUGR. Prevalence was higher according to Fenton in IUGR (36.5 vs. 35.1%), in static EUGR (73.8 vs. 59.3%), and in dynamic EUGR (44.3 vs. 29.3%). Despite observing low prevalence of EUGR when IW-21 was used to define EUGR, a statistical association between neonatal morbidity and diagnosis of EUGR was observed. Conclusion: The Fenton and IW-21 concordance for IUGR is good. IW-21 is more restrictive than Fenton in EUGR. Patients diagnosed by IW-21 as EUGR are more likely to have neonatal morbidity, especially if we use EUGR dynamic definition. In our study, we cannot conclude that one graph is better than the other.